Deformation and cyclic buckling capacity of external replaceable hysteretic dampers for unbonded post-tensioned precast concrete walls - Bedriñana, Luis Alberto (2021)
The financial support of the Peruvian National Council of Science, Technology, and Technological Innovation (CONCYTEC/CIENCIACTIVA) for the doctoral studies of the first author at Kyoto University, where this research was conducted, is acknowledged.